A corpus-assisted discourse analysis case study of public opinion on climate change in Malaysia - Nor Fariza Mohd Nor,; Tasha Erina Taufek,; Azhar Jaludin,; Jamaluddin Aziz,; Lam, Kuok Choy; Sabrina Tiun, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Climate change is a global emergency that necessitates urgent action from policymakers and the public. Public opinion plays a crucial role in shaping climate change policy, making it essential to understand how people perceive and respond to the issue. Studies on public opinion on climate change are emerging, but are lacking in examining linguistic aspects. The present study intends to conduct a linguistic analysis of public opinion news to identify public recommendations on climate change issues, by identifying themes in opinion news on climate change. The analysis focused on directive verbs and modal verbs, and examined how the general public linguistically expressed their recommendations. 136 news articles from the New Straits Times Malaysia were analysed using a corpus-assisted discourse analysis approach. The findings revealed that the dominant themes are government action, followed by education and awareness, protecting natural resources, encouraging sustainable lifestyle, transitioning to renewable energy, and reducing greenhouse gas emissions. The public's overwhelming emphasis on government action, indicates a strong demand for policy restructuring and enactment to address climate change. While there is increasing awareness and interest in learning about climate change, the study raises concerns about the limited attention given to themes such as encouraging sustainable living, protecting natural resources, transitioning to renewable energy, and reducing greenhouse gas emissions, suggesting a need for further education and awareness campaigns to bridge these knowledge gaps and promote holistic climate action. The results provide insights into Malaysian public opinion on climate change, which can assist policymakers in developing effective policies and communication strategies.